A Review on Micro-manufacturing, Micro-forming and Their Key Issues - A. R., Razali; Qin, Yi (Elsevier Ltd, 2013)
Micro-manufacturing has received good attention globally in terms of its manufacturing methods/processes. One of the most popular micro-manufacturing processes is micro-forming. Many efforts have been focused on micro-forming, mainly on the micro-stamping process due to the process itself contributing numerous products, especially in its conventional macro-process. Most every-day products are made by this process. Although there were efforts made to realize micro-forming for industrial application, the technology itself was seen as being insufficiently mature. Much development work needed to be done, specifically to develop a fully-automated high-volume production micro-forming machine, which is reliable and at all times ready for operation in terms of it processes, tooling, and material-handling to ensure the successful production of micro-products. The paper addresses key issues encountered by researchers worldwide on both micro-manufacturing, specifically micro-forming.